Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

AlgaePath 2.0: An updated database for revealing algal coding and non-coding gene interactions in metabolic pathways - Kuan-Chieh Tseng; Wen-Lin Wang; Yen-Lin Shen; Hung-Teng Wang; Ching-Ya Yuan; Chien-Wen Yang; Ching-Nen Nathan Chen; Wen-Chi Chang (Algal Research, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Cold Atmospheric Plasma as a Non-Thermal and Biocompatible Disinfection Strategy for Ultrasound Transducers - Ching-Yuan Lin; Kuan-Yi Lee; Dong-Jin Li; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Entropy-stabilized multi-element 2D TMDs: Tunable electronics and enhanced thermal stability - Ching-Wei Chin; Chong-Chi Chi; Kai-Yuan Hsiao; Yi-Hsin Fang; Dun-Jie Jhan; Chun-Hui Lin; Ming-Pei Lu; Ming-Yen Lu (Chemical Engineering Journal, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Photodegradation of tetracycline using O-gCN/SiC/PVDF thin film photocatalysts irradiated with simulated sunlight - Yung-Dun Dai; You-Lin Chou; Ching Yuan (Process Safety and Environmental Protection, 2025)

Understanding tractography in edematous brain regions: challenges and solutions - Shin Tai Chong; Joseph Yuan-Mou Yang; Ching-Po Lin (Brain Structure and Function, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Enhanced removal of sulfamethoxazole via adsorption and photodegradation using biochar-modified iodine-doped TiO2 photocatalysts under simulated sunlight - Yung-Dun Dai; Jia-Hou Lin; Chung-Hsuang Hung; Ching Yuan (Process Safety and Environmental Protection, 2024)

Investigation of verapamil-induced cardiorenal dysfunction and compensatory ion regulation in zebrafish embryos - Jiun-Lin Horng; Bu-Yuan Hsiao; Wen-Ting Lin; Tzu-Ting Lin; Ching-Yen Chang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Protective Effects of Roselle Aqueous Extracts against UV-Induced Damage in Zebrafish Fins - I-Ting Lee; Ching-Yuan Huang; Wei-Lin Su; Tran M. Truong; Chi-Chung Wen; Bo-Chang Wang; Yau-Hung Chen (Fishes, 2024)
(1) Background: Roselle (Hibiscus sabdariffa) is a flowering plant reported to have anti-obesity, antioxidant, antibacterial, and anti-inflammatory effects. This study aims to evaluate the UV-absorbing and antioxidant activities of roselle aqueous extracts (RAE) and test the protective effects of RAE against UV radiation in zebrafish embryos. (2) Methods: DPPH assay and UV-spectrum methods were applied to evaluate the antioxidant and UV-absorbing activities, respectively. The protective effects of RAE were evaluated using fin morphology recording, Kaplan–Meier analysis, and Cox proportional hazards regression. Real-time PCR experiments were also applied to detect both the UV- and RAE-induced gene expressions. (3) Results: Our results show that (i) RAE had UV-absorbing abilities and significantly reduced ROS production in vitro; (ii) the mean times of malformed fins in the UV + RAE (36 and 48 ppm) groups were 3.56 and 4.44 days, respectively, and were prolonged compared to those in the UV-only group (3.36 days); (iii) zebrafish in the UV + RAE (36 and 48 ppm) groups were 0.963 and 0.496 (p

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

A practical lateral spreading pressure model for piles in inclined liquefied ground - Jiunn-Shyang Chiou; Ching-Lin Chen; Jing Ling Ng; Yuan-Man Hsu (Engineering Structures, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Different microbial communities in paddy soils under organic and nonorganic farming - Jimmy Kuo; Daniel Liu; Wei Hao Wen; Ching Yuan Chiu; Wanyu Chen; Yun Wen Wu; Fang-Ting Lai; Chorng-Horng Lin (Brazilian Journal of Microbiology, 2024)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

InSAR-based investigation on spatiotemporal characteristics of river sediment behavior - Shih-Yuan Lin; Shih-Teng Chang; Ching-Fang Lee (Journal of Hydrology, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Viscous Flow Fields Induced by the Run-Up of Periodic Waves on Vertical and Sloping Seawalls - Chun-Yuan Lin; Ching-Jer Huang; Tai-Wen Hsu (Journal of Marine Science and Engineering, 2022)
Unsteady two-dimensional Reynolds Averaged Navier-Stokes (RANS) equations coupled with the k−ε turbulence model was developed to simulate the viscous flow field near seawalls. The complex free-surface configuration was captured using the particle level set method (PLSM). An innovative solid-fluid coupling method was employed to mimic the solid-fluid interaction on fixed Cartesian grids. The proposed numerical model was applied to investigate the viscous flow fields induced by periodic waves propagating on three different seawalls, including vertical and steep seawalls, which are commonly designed in Taiwan with slopes of 1:2 and 1:5. The results reveal that the wave run-up height is closely related to Iribarren number and breaking wave. Partial standing wave or asymmetric recirculating cells in front of a steep seawall lose symmetry with increasing slope. The wave pressure on the seawall face increases as the Ursell number or seawall slope increases. The undertow caused by breaking waves has a significant effect on the bottom shear stress in front of the seawall.

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Optimization of Groundwater Quality Monitoring Network Using Risk Assessment and Geostatistic Approach - Shih -Ching Wu; Kai-Yuan Ke; Hsien-Tsung Lin; Yih-Chi Tan (Water Resources Management, 2017)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Combined effect of rice genotypes and soil characteristics on iron plaque formation related to Pb uptake by rice in paddy soils - Fang-Lin Li; Ching-Ming Yang; Chien-Hui Syu; Dar-Yuan Lee; Ben-Jei Tsuang; Kai-Wei Juang (Journal of Soils and Sediments, 2016)

Spatial optimization procedure for land-use arrangement in a community based on a human comfort perspective - Pei-Yuan Chen; Ching-Pin Tung; Wei-Chih Lin; Yuan-Hua Li (Paddy and Water Environment, 2016)

Avian reovirus S1133-induced apoptosis is associated with Bip/GRP79-mediated Bim translocation to the endoplasmic reticulum - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Yo-Chia Chen; Chi-I Chang; Wen-Ling Shih (Apoptosis, 2015)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Estimating Pumping Rates and Identifying Potential Recharge Zones for Groundwater Management in Multi-Aquifers System - Hsien-Tsung Lin; Kai-Yuan Ke; Yih-Chi Tan; Shih-Ching Wu; Gao Hsu; Po-Chia Chen; Shi-Ting Fang (Water Resources Management, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

An Adaptation Due to Climate Change in Southwest Coast of Taiwan - Yuan-Jyh Lan; Tai-Wen Hsu; Yue-Chen Lin; Ching-Jer Huang (Coastal Management, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Avian reovirus S1133-induced DNA damage signaling and subsequent apoptosis in cultured cells and in chickens - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Chi-I Chang; Jue-Liang Hsu; Ming-Huei Liao; Jeng-Woei Lee; Wen-Ling Shih (Archives of Virology, 2011)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

Characteristics analysis for the flash flood-induced debris flows - Chen Chien-Yuan; Chen Lien-Kuang; Yu Fan-Chieh; Lin Sheng-Chi; Lin Yu-Ching; Lee Chou-Lung; Wang Yu-Ting; Cheung Kei-Wai (Natural Hazards, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

Improving debris flow monitoring in Taiwan by using high-resolution rainfall products from QPESUMS - Chien-Yuan Chen; Lee-Yao Lin; Fan-Chieh Yu; Ching-Sheng Lee; Chun-Chieh Tseng; An-Hsiang Wang; Kei-Wai Cheung (Natural Hazards, 2007)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Polymorphism for Transforming Growth Factor Beta 1-509 (TGF-B1-509): Association with Endometriosis - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Ching-Tien Peng; Lian-Shun Yeh; Cheng-Chieh Lin (Biochemical Genetics, 2005)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)